2021
DOI: 10.2147/oajc.s316009
|View full text |Cite
|
Sign up to set email alerts
|

When Do Nigerian Women of Reproductive Age Initiate and What Factors Influence Their Contraceptive Use? A Contextual Analysis

Abstract: Background: Contraceptive use initiation and continuation is one of the major interventions for reducing maternal deaths worldwide. Nigeria aimed to achieve a 27% prevalence rate of modern contraceptive uptake by 2020, however, this seems to have remained unachieved. The objective of this study was to investigate when Nigerian women initiate contraceptive use and its associated factors, using nationally representative data. Methods: Data on 11,382 Nigerian women (aged 15-49 years) from the 2017 Performance Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Women's place of residence and their community early marriage status were predicted time interval-to-contraceptive use after childbirth when other variables were controlled for. As in other studies ( 56 , 57 ), rural women took a long time to adopt modern methods postpartum than their counterparts. Our findings contrast somewhat with several prior studies ( 35 , 37 ) that have identified no difference in time to modern contraceptive use among rural and urban residents.…”
Section: Discussionsupporting
confidence: 62%
“…Women's place of residence and their community early marriage status were predicted time interval-to-contraceptive use after childbirth when other variables were controlled for. As in other studies ( 56 , 57 ), rural women took a long time to adopt modern methods postpartum than their counterparts. Our findings contrast somewhat with several prior studies ( 35 , 37 ) that have identified no difference in time to modern contraceptive use among rural and urban residents.…”
Section: Discussionsupporting
confidence: 62%
“…The survey focused on urban centers with a high population of adolescents in three Nigerian states namely Kaduna in the Northwest region, and Lagos and Oyo in the Southwest. These States were selected based on their relatively high records of mCPR ( 23 ) and high burdens of urban slums.…”
Section: Methodsmentioning
confidence: 99%
“…Existing studies have examined factors associated with low mCPR which include poverty, low level of education, rural residence, socioeconomic status, and awareness of family planning methods ( 22 , 23 ). Most of the studies have focused on all women, irrespective of their place of residence, with no consideration for adolescents, especially those in the slums, who are of varied socioeconomic class, largely unmarried, but engaging in high sexual activity and at risk of unwanted pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, the prevalence of modern contraceptive use was 14.2%. 6 According to Nigeria Demographic and Health Survey (NDHS), the use of modern contraceptive method was higher among sexually active unmarried women (28%) than among married women (12%). Among currently married women, the prevalence of contraception, regardless of method, was 17%.…”
Section: Introductionmentioning
confidence: 99%